Urban and Agricultural Communities: Opportunities for Common Ground - Butler, Lorna Michael; Maronek, Dale M.; Bills, Nelson; Davis, Tim D.; Freedgood, Julia; Howell, Frank M.; Kelly, John; Libby, Lawrence W.; Pothukuchi, Kameshwari; Relf, Diane; Thomas, John K.; Thompson, Paul B. (Council for Agricultural Science and Technology (CAST), 2002)
The changing role of agriculture in urban settings is considered in this comprehensive report written by a twelve-member task force. The report frames “urban agriculture” in both historical and contemporary American society, providing a picture of geographic, demographic, and economic changes in rural and metropolitan life. Policy issues such as land preservation, alternative market opportunities, sprawl, taxation, and food security are considered. Research and educational challenges are presented for consideration by those at institutions of higher education, including land-grant universities.